Proceedings of the 51st Hawaii International Conference on System Sciences 2018
DOI: 10.24251/hicss.2018.682
|View full text |Cite
|
Sign up to set email alerts
|

A Wheelbarrow Full of Frogs: Understanding Portfolio Management for Agile Projects

Abstract: Organizations increasingly embrace agile approaches for IT projects, replacing rigid formal stage-gate control by flexible output-orientation. This challenges established program or portfolio management approaches that largely rely on consolidated (stage-gate) project metrics. Based on seven case studies of large Dutch organizations we explore these challenges and the organizational responses towards a new approach to portfolio management for agile projects. Data-collection is guided by four propositions deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
(57 reference statements)
2
3
0
Order By: Relevance
“…This has also been theorized by Weill and Ross [32] who claim that proper organizational structure and IT governance design allow for simultaneously achieving effectiveness (IT business value) and efficiency (return on assets) [32]. In line with our discussion in the previous sections, IT infrastructure flexibility has a positive and significant effect on agility [26], where the transformation to organizational agility leads to more focus on business value and less on IT project control [19]. When looking at innovation, a stronger reliance on IT governance mechanisms -in the form of boards and committees-leads to less process or product innovation [33].…”
Section: P1: Unclear Governance Processes Cause Inertia When Organizasupporting
confidence: 79%
See 2 more Smart Citations
“…This has also been theorized by Weill and Ross [32] who claim that proper organizational structure and IT governance design allow for simultaneously achieving effectiveness (IT business value) and efficiency (return on assets) [32]. In line with our discussion in the previous sections, IT infrastructure flexibility has a positive and significant effect on agility [26], where the transformation to organizational agility leads to more focus on business value and less on IT project control [19]. When looking at innovation, a stronger reliance on IT governance mechanisms -in the form of boards and committees-leads to less process or product innovation [33].…”
Section: P1: Unclear Governance Processes Cause Inertia When Organizasupporting
confidence: 79%
“…Due to the novelty of these platforms new challenges occurred in stage 4 ( fig. 1 [41] as well as a need for a supportive IT function to effectively support digitization for the long term [7], focused on increasing the business value [19]. Moreover, we observed that roles and responsibilities are scattered throughout the organization, as well as outsourced to external strategic partners.…”
Section: P3: It-process Controlsmentioning
confidence: 90%
See 1 more Smart Citation
“…On the other hand, in those organizations that already had more mature governance implementations, they showed different dynamics fully in line with the findings of (Smeekes et al, 2018). We have grouped the findings into the broad patterns we have identified as shown below: 1.…”
Section: Organisations With More Evolutionary Approaches To Governancesupporting
confidence: 63%
“…The second relevant publication comes from Smeekes et al (2018); it addresses various aspects of agile portfolio management projects, based on seven case studies conducted in large Dutch organizations. Although these studies focused on IT portfolio management projects, they contain general descriptive and contextual information relevant to the objective of this paper.…”
Section: Research Summarymentioning
confidence: 99%